The Impact of Financial Technology on Financial Inclusion in Islamic Banks: Analytical Study of Bahrain Islamic Bank for the Period (2019-2022) - bekkouche, chaima; Bouadou , Fatima (Journal of Research in Finance and Accounting, 2025)
This study aimed to understand the reality of financial technology in Islamic banks and its contribution to enhancing financial inclusion. To achieve the study's objectives, a descriptive approach was adopted by elucidating the theoretical frameworks of financial technology and financial inclusion in Islamic banks. Additionally, an analytical approach was employed through a study of Bahrain Islamic Bank over the period extending from 2019 to the year 2022. The study concluded that Bahrain Islamic Bank relies on innovative financial technology by employing various digital financial services and products, leading to an elevation in the level of financial inclusion. Consequently, financial technology is considered one of the most important mechanisms for implementing and enhancing financial inclusion in Islamic banks.